Pengaruh Attitude, Subjective Norm Dan Perceived Behavioral Control Terhadap Minat UMKM Dalam Penyusunan Laporan Keuangan - Srikalimah Srikalimah; Rike Selviasari; Dewi Wungkus Antasari; Musabihul Qowi (Politeknik Ganesha Medan, 2023)
The interest of MSMEs in the preparation of financial statements has an important role in making the right decisions and increasing stakeholder confidence. The purpose of this study is to investigate the factors that affect the interest of MSMEs in preparing financial statements. As well as knowing the influence of attitudes, subjective norms, perceptions of behavior control both partially and simultaneously on the interest of MSMEs in the preparation of financial statements. This research method is a descriptive quantitative approach with primary data sources through the dissemination of questionnaires with a sample of 100 MSME actors. Data analysis using descriptive statistics using SPSS. The results showed that partially or simultaneously attitude, subjective norm and perceived behavioral control have a positive and significant effect on the interest of MSMEs in the preparation of financial statements in Kediri. The results of this study provide empirical evidence about the factors that can affect interest in the preparation of financial statements.